2019
DOI: 10.1590/1413-812320182412.04112018
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da atenção secundária em endodontia em um Centro de Especialidades Odontológicas (CEO)

Abstract: Resumo Objetivou-se avaliar a atenção secundária em endodontia em um Centro de Especialidades Odontológicas (CEO) de Belo Horizonte (MG). A coleta de dados utilizou dois formulários: (1) sobre o tratamento endodôntico, preenchido pelos endodontistas; (2) sobre o tratamento restaurador, com dados dos prontuários. O programa SPSS 19.0 foi utilizado para analisar os resultados por meio de frequência e percentis. Foram finalizados 452 tratamentos endodônticos em pacientes adultos. Os pacientes apresentaram mediana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
3
0
4
Order By: Relevance
“…The findings indicated that the median waiting time for access to specialized dental care in the Brazilian healthcare system ranged from 5 to 30 days across specialties. The longest waiting list was for endodontic care, which is consistent with other reports from different years and locations in Brazil 16‐18 . This is particularly relevant in the context of national oral health policies since initiatives to reduce the waiting list can directly impact health outcomes nationwide.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings indicated that the median waiting time for access to specialized dental care in the Brazilian healthcare system ranged from 5 to 30 days across specialties. The longest waiting list was for endodontic care, which is consistent with other reports from different years and locations in Brazil 16‐18 . This is particularly relevant in the context of national oral health policies since initiatives to reduce the waiting list can directly impact health outcomes nationwide.…”
Section: Discussionsupporting
confidence: 86%
“…The longest waiting list was for endodontic care, which is consistent with other reports from different years and locations in Brazil. [16][17][18] This is particularly relevant in the context of national oral health policies since initiatives to reduce the waiting list can directly impact health outcomes nationwide. While the literature has shown inarguably that long waiting times are associated with increased absenteeism, high costs/economic burden, and health issues, 19,20 this remains poorly debated in the field of oral health.…”
Section: Variablesmentioning
confidence: 99%
“…Um período de 5 meses de espera por um tratamento endodôntico, como encontrado neste estudo, pode gerar várias consequências negativas como a busca constante do paciente por tratamentos de urgência com intuito de alívio da dor, sobrecarregando a atenção primária com esta demanda, além da possibilidade de ocorrer fratura do elemento dental e/ou desistência do paciente pelo tratamento. Estes dois últimos fatores podem resultar na exodontia do elemento dentário (Magalhães et al, 2019).…”
Section: Discussionunclassified
“…Embora tenha tido um aumento no número de CEOs implantados, a rede assistencial da atenção secundária em saúde bucal não acompanhou o crescimento gradativo da oferta dos serviços da atenção básica através da expansão da cobertura das equipes de saúde bucal no Sistema Único de Saúde (SUS). Desta forma, o baixo número de profissionais na especialidade de endodontia no cenário atual dos grandes centros do país não é capaz de atender a demanda, acarretando a formação de longas filas de espera nos CEOs associado a falha no próprio mecanismo de referência dos pacientes entre os níveis de atenção 30 , ou à própria dificuldade do acesso, que podem levar à desistência por parte do usuário que pode comprometer a rede de atenção à saúde bucal.…”
Section: Discussionunclassified